MDR Sepsis in Critically Ill Patient: Global Trend and Specific Challenges for Bangladesh (Bangladesh Critical Care Journal, 2025)
Multidrug-resistant (MDR) sepsis poses an escalating global health threat, particularly in intensive care units (ICUs) where vulnerable patient populations are at heightened risk due to frequent invasive procedures, immunosuppression, and prolonged hospitalization. This review explores the global burden and rising prevalence of MDR sepsis among ICU patient population, with a specific focus on challenges and implications in Bangladesh. Ventilator-associated pneumonia (VAP), catheter-associated urinary tract infections (CAUTIs), and central-line-associated bloodstream infections (CLABSIs) are identified as the predominant ICU-acquired infections contributing to MDR sepsis. This review highlights alarming rates of antimicrobial resistance (AMR) among Gram-negative and Gram-positive pathogens, with Bangladesh reporting disproportionately higher resistance levels compared to global trends. Inadequate antimicrobial stewardship, poor infection prevention and control (IPC) practices, and lack of robust regulatory oversight exacerbate the crisis in resource-limited settings like Bangladesh. Furthermore, the review emphasizes the importance of adopting a multidisciplinary and One Health approach, strengthening surveillance systems, enhancing IPC infrastructure, reforming medical education, and raising public and political awareness. Addressing MDR sepsis in Bangladesh demands urgent policy-level interventions, international collaboration, and sustainable investment in healthcare capacity building to mitigate this silent yet deadly epidemic.Bangladesh Crit Care J September 2025; 13 (2): 110-114